Heterogeneity in Private Sector Health Care and its Implications on Urban Poor. (March 2014) - George, Mathew
Private sector health care attains more attention in the current context due to its changing nature and characteristics. One such characteristic is the heterogeneity in terms of care prevalent within the private sector. Heterogeneity within private sector has been a challenge not only in terms of its understanding but also the way it interacts with the policies on the regulation of the health services system. The present study examines the nature of this heterogeneity based on the care rendered for an acute illness, namely, fever. The study was carried out in an urban setting and the severity of illness examined using duration of illness as a proxy. The results reveal that the cost of treatment in secondary level hospitals is higher than those at the primary level hospitals irrespective of the severity. The higher cost is contributed not only by the quantum of investigations and procedures, but also due to higher cost per procedure. It was found that the poor utilize more services at the primary level, whereas the secondary level hospital was mostly utilized by the better off. On the contrary, the policies of the government have been beneficial mostly for the secondary level hospitals.